BENTURAN SUARA DAN MAKNA RUMAH DALAM CERPEN RUMAH-RUMAH NAYLA KARYA DJENAR MAESA AYU: KAJIAN DIALOGISME BAKHTIN - Faizin, Ahmad; Maulidia, Zulia Khikmatul (Universitas Negeri Surabaya, 2025)
This research aims to analyze the meaning of home in the short story Rumah-Rumah Nayla by Djenar Maesa Ayu through Bakhtin's narratological perspective, particularly the concepts of dialogism and polyphony. The story represents home not merely as a physical dwelling, but as a space layered with voices, experiences, and meanings that often clash with each other. This study is qualitative research using narrative analysis to explore the various voices and consciousnesses of its characters, such as Nayla as a victim, wife, mother, and writer, as well as the voices of her husband and children. The results show that each voice in the story stands side by side without any single voice dominating. The interaction and collision among these voices create a complex and dynamic dialogic space where the meaning of home becomes fluid, open, and continuously shaped by each character’s personal experience. Thus, the story affirms that the meaning of home is dialogic and never singular, but always open to new interpretations in accordance with each individual’s experience.